Testing for a single-factor stochastic volatility in bivariate series - Masaru Chiba; Masahito Kobayashi (Journal of Risk and Financial Management, 2013)
This paper proposes the Lagrange multiplier test for the null hypothesis thatthe bivariate time series has only a single common stochastic volatility factor and noidiosyncratic volatility factor. The test statistic is derived by representing the model in alinear state-space form under the assumption that the log of squared measurement error isnormally distributed. The empirical size and power of the test are examined in Monte Carloexperiments. We apply the test to the Asian stock market indices.
Keywords: C12; C32; C58; 330; stochastic volatility model; Kalman filter; Lagrange multiplier test